Welcome to Westonci.ca, the place where your questions find answers from a community of knowledgeable experts. Get immediate and reliable solutions to your questions from a community of experienced experts on our Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the quadratic equation given the roots [tex]\( x = 2 + i \)[/tex] and [tex]\( x = 2 - i \)[/tex], we can use the fact that for a quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex], the sum of the roots [tex]\( (x_1 + x_2) \)[/tex] is equal to [tex]\( -b/a \)[/tex] and the product of the roots [tex]\( (x_1 \cdot x_2) \)[/tex] is equal to [tex]\( c/a \)[/tex].
Given:
- Roots [tex]\( x_1 = 2 + i \)[/tex] and [tex]\( x_2 = 2 - i \)[/tex]
Step-by-step solution:
1. Sum of the roots:
Sum [tex]\( (x_1 + x_2) = (2 + i) + (2 - i) = 4 \)[/tex]
Therefore, [tex]\( -b/a = 4 \)[/tex].
2. Product of the roots:
Product [tex]\( (x_1 \cdot x_2)= (2 + i)(2 - i) = 2^2 - i^2 = 4 - (-1) = 4 + 1 = 5 \)[/tex]
Therefore, [tex]\( c/a = 5 \)[/tex].
3. Considering the standard form of the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex], and typically [tex]\( a = 1 \)[/tex] for simplicity (which does not change the equation’s nature), we can write:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -4 \)[/tex] (from [tex]\( -b = 4 \)[/tex] hence [tex]\( b = -4 \)[/tex])
- [tex]\( c = 5 \)[/tex] (from [tex]\( c = 5 \)[/tex])
Putting these values into the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 1x^2 - 4x + 5 = 0 \][/tex]
Therefore, the quadratic equation with the roots [tex]\( x = 2 \pm i \)[/tex] is:
[tex]\[ x^2 - 4x + 5 = 0 \][/tex]
Given:
- Roots [tex]\( x_1 = 2 + i \)[/tex] and [tex]\( x_2 = 2 - i \)[/tex]
Step-by-step solution:
1. Sum of the roots:
Sum [tex]\( (x_1 + x_2) = (2 + i) + (2 - i) = 4 \)[/tex]
Therefore, [tex]\( -b/a = 4 \)[/tex].
2. Product of the roots:
Product [tex]\( (x_1 \cdot x_2)= (2 + i)(2 - i) = 2^2 - i^2 = 4 - (-1) = 4 + 1 = 5 \)[/tex]
Therefore, [tex]\( c/a = 5 \)[/tex].
3. Considering the standard form of the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex], and typically [tex]\( a = 1 \)[/tex] for simplicity (which does not change the equation’s nature), we can write:
- [tex]\( a = 1 \)[/tex]
- [tex]\( b = -4 \)[/tex] (from [tex]\( -b = 4 \)[/tex] hence [tex]\( b = -4 \)[/tex])
- [tex]\( c = 5 \)[/tex] (from [tex]\( c = 5 \)[/tex])
Putting these values into the quadratic equation [tex]\( ax^2 + bx + c = 0 \)[/tex]:
[tex]\[ 1x^2 - 4x + 5 = 0 \][/tex]
Therefore, the quadratic equation with the roots [tex]\( x = 2 \pm i \)[/tex] is:
[tex]\[ x^2 - 4x + 5 = 0 \][/tex]
Thank you for visiting our platform. We hope you found the answers you were looking for. Come back anytime you need more information. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.